Pacing Profiles in Competitive Track Races: Regulation of Exercise Intensity Is Related to Cognitive Ability - Van Biesen, Debbie; Hettinga, Florentina J.; McCulloch, Katina; Vanlandewijck, Yves (Frontiers in Physiology, 2016)
Pacing has been defined as the goal-directed regulation of exercise intensity over an exercise bout, in which athletes need to decide how and when to invest their energy. The purpose of this study was to explore if the regulation of exercise intensity during competitive track races is different between runners with and without intellectual impairment, which is characterized by significant limitations in intellectual functioning (IQ≤75) and adaptive behavioral deficits, diagnosed before the age of 18. The samples included elite runners with intellectual impairment (N= 36) and a comparison group of world class runners without impairment (N= 39), of which 47 were 400m runners (all male) and 28 were 1500m-runners (15 male and 13 female). Pacing was analysed by means of 100m split times (for 400m races) and 200m split times (for 1500m races). Based on the split times, the average velocity was calculated for four segments of the races. Velocity fluctuations were defined as the differences in velocity between consecutive race segments. A mixed model ANOVA revealed significant differences in pacing profiles between runners with and without intellectual impairment (p<.05). Maximal velocity of elite 400m runners with intellectual impairment in the first race segment (7.9 ± 0.3 m/s) was well below the top-velocity reached by world level 400m runners without intellectual impairment (8.9 ±0.2 m/s), and their overall pace was slower (F=120.7, p<.05). In addition, both groups followed a different pacing profile and inter-individual differences in pacing profiles were larger, with differences most pronounced for 1500m races. Whereas male 1500m-runners without intellectual impairment reached a high velocity in the first 100m (7.2±0.1 m/s), slowly decelerated in the second race segment (-0.6±0.1 m/s), and finished with an end sprint (+0.9±0.1 m/s); the 1500m runners with intellectual impairment started slower (6.1±0.3 m/s), accelerated in the second segment (+ 0.2±0.7 m/s), and then slowly decreased until the finish (F=6.8, p<.05). Our findings support the hypothesis that runners with intellectual impairment have difficulties to efficiently self-regulate their exercise intensity. Their limited cognitive resources may constrain the successful integration of appropriate pacing strategies during competitive races.